Kidney Injury: Focus on Molecular Signaling Pathways - Liu, Wei; Hu, MengDi; Wang, Le; Mirzaei, Hamed (Current Medicinal Chemistry, 2024)
Acute kidney injury (AKI) is a syndrome in which kidney function reduces suddenly. This syndrome which includes both structural changes and loss of function may lead to chronic kidney disease (CKD). Kidney regeneration capacity depends on the cell type and severity of the injury. However, novel studies indicated that regeneration mostly relies on endogenous tubular cells that survive after AKI. Regenerative pharmacology requires a great knowledge of fundamental processes involved in the development and endogenous regeneration, leading to a necessity for investigating related signaling molecules in this process. Regulatory non-coding RNAs (ncRNAs) including microRNAs (miRNAs), long non-coding RNAs (lncRNAs), and circular RNAs (circRNAs) are currently known as critical regulators of gene expression in various cellular processes, and this regulatory function is also observed in nephrotic tissue, following damaging insults, which may promote or inhibit the progression of damage. Thus, studying signaling molecules and pathways involved in renal injury and repair results in a comprehensive prospect of these processes. Moreover, these studies can lead to new opportunities for discovering and enhancing therapeutic approaches to renal diseases. Herein, we review studies dealing with the role of different signaling pathways involved in renal injury. Besides, we discuss how some signaling pathways are useful for the repair process following AKI.
Keywords: repair